Penerapan Terapi Foot Massage Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Ruang ICU Di RS PKU Muhammadiyah Karanganyar - Inggit Zulkharisma; Fida’ Husain; Andri Setiyawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Blood pressure is an important indicator in assessing the cardiovascular system and the performance of a person's body so it is necessary to know that someone has hypertension. There are 1.28 billion adults with hypertension in the world in 2021 who suffer from hypertension. While the number of patients in the ICU who suffered from hypertension in the last 1 year was 140 patients. Based on these conditions, management is needed to reduce blood pressure by providing Foot Massage intervention. Objective: To find out the results of the implementation of giving Foot Massage on Lowering Blood Pressure in Hypertensive Patients in the ICU Room at PKU Muhammadiyah Karanganyar Hospital. Method : This type of research is a case study of foot massage in hypertensive patients. Results: The results of the implementation of Foot Massage found a decrease in blood pressure in both rospenden Mr. M from 145/90mmHg to 125/80mmHg, and Mrs. W 159/100mmHg to 130/90mmHg Conclusion: There are differences in blood pressure in hypertensive patients after Foot Massage therapy at PKU Muhammadiyah Karanganyar Hospital.